Existence of Mild and Classical Solutions of Nonlinear Integrodifferential Equation in Banach Space - Kumar, Kamalendra; Kumar, Rakesh (Kathmandu University Journal of Science, Engineering and Technology, 2014)
In this paper, we use the theory of analytic semigroups to prove the existence and uniqueness of local mild and then classical solution of a class of nonlinear integrodifferential equations in Banach space.